Popular Music in Audio-visual Advertising: A Study of the Roles and Functions of Lyrics in TV-commercials - Anisimova, Tatiana; Müllern, Tomas; Plachkova, Tonya (Advances in Social Sciences Research Journal, 2014)
The use of popular songs is one of the most common methods in connecting with the audience in mass advertising. Advertisers are in search for the right melody or a song that can best connect a product and a brand to consumers’ aspirations. The extant literature advocates the importance of a match or congruency between the song in the advertisement and a brand to avoid misinterpretation of the advertising message. Based on the analysis of 96 Levi’s TV commercials, the current study looked at how lyrics in popular music of TV commercials are used and how they fit with the overall brand message and related elements of the commercial.